Adipose stromal cells increase insulin sensitivity and decrease liver gluconeogenesis in a mouse model of type 1 diabetes mellitus - Hsiao-Chi Lai; Yen-Ju Lee; Pei-Hsuan Chen; Chia-Hua Tang; Lee-Wei Chen (Stem Cell Research & Therapy)
Abstract Background Diabetic ketoacidosis (DKA) is a serious complication of hyperglycemic emergency caused by insulin deficiency through accelerated liver gluconeogenesis and glycogenolysis. DKA is most common in type 1 diabetes (T1D). Transplantation of islet cells and pancreas is an alternative to insulin injection for treating T1D. However, this alternative is only suitable for some patients. This study investigated the effects and mechanisms of adipose stromal vascular fraction (SVF) cells on liver gluconeogenesis and insulin sensitivity in an insulin-dependent T1D animal model. Methods SVF cells were obtained from wild-type inguinal adipose tissue and transplanted into the peritoneal cavity of type I diabetic Akita (Ins2 Akita) mice. Results We found that transplantation of 5 × 106 SVF cells from wild-type adipose tissue significantly downregulated proinflammatory genes of TNF-α, IL-1β, IL-33, iNOS, and DPP4 in the liver and upregulated anti-inflammatory factors IL-10 and FOXP3 in blood serum and liver tissue 7 days after injection. Moreover, we found that the expression levels of G6pc and Pck1 were significantly decreased in the Akita mice livers. Furthermore, the intraperitoneal insulin tolerance test assay showed that diabetic Akita mice significantly had increased insulin sensitivity, reduced fasting blood glucose, and restored glucose-responsive C-peptide expression compared with the control Akita group. This result was noted 14 days after administration of 5 × 106 or 1 × 107 SVF cells from wild-type adipose tissue into diabetic Akita mice. Conclusions Together, these findings suggest that adipose tissue-derived SVF cells could suppress liver inflammation, regulate liver gluconeogenesis, and improve insulin sensitivity in an animal model with T1D. Therefore, adipose SVF cells may be novel cellular therapeutic alternatives to maintain steady liver gluconeogenesis in T1D.